Manual for Modified CAMDT/DSSAT Crop Yield Prediction Model - Garanganga, Bradwell; Nyakutambwa, Trymore (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Crop capability prediction modelling platforms used in this User Guide are the Climate-AgricultureModelling and Decision Tool (CAMDT) as the weather generator; i.e., it is an algorithm to make temporal downscaling. CAMDT is used to drive the Decision Support System for Agrotechnology Transfer (DSSAT), the crop weather simulation model. CAMDT/ DSSAT platforms are very sensitive to the data formats, i.e., data must be compatible for ingestion into these environments. In this regard, there will be need to preprocess the climatological data for exporting into CAMDT/DSSAT programmes. For instance, use data downloaded from NASA (National Aeronautics and Space Administration) website (https://power.larc.nasa.gov/data-access-viewer/). There is need for downloaded daily climatological data to be manipulated into and across both MS Excel and CSV environments. The authors have already reformatted climatological data from Mapai, Mozambique, provided with this note. The necessary steps to be followed in order to make the data formats compatible with CAMDT/DSSAT are presented in the following sections.